Sakralität im Wandel Religiöse Bauten im Stadtraum des 21. Jahrhunderts in Deutschland - Löffler, Beate; Sharbat Dar, Dunja (De Gruyter, 2022)
The sacred spaces of our cities have become more diverse in recent decades. Alongside established institutions, new voices are claiming participation in the coexistence of religious ideas as well as in architectural expression.